The Worldwide Expansion of Evaluation: a World of Possibilities for Rural Development - Vidueira, Pablo (2013)
The growing importance of the evaluation field is exemplified by its increasing use in international organizations and public policies at a regional, national and local level, as well as by the exponential growth of evaluation societies around the world. Focusing on rural development, this expansion is due to the utility of evaluation in providing evidence to help in the decision-making and improve interventions, as well as being a value system that establishes criteria and explicit standards by which to judge these interventions. This paper aims to provide clarity on these aspects through a comprehensive analysis of the evolution and the current situation of the evaluation field. The literature reviewed and our evaluation experiences confirm the evaluation’s ability to provide a scientific basis to the decision-making in rural development programmes.